Mobile-Based Project Citizen: Innovating Civic Education for the Digital Era - Fajar Rahmad; Mukhamad Murdiono; Supri Hartanto; Oktana Wahyu Perdana; Afgha Okza Eriranda (STAI Hubbulwathan Duri, 2025)
This study aims to develop a mobile-based learning media to support the implementation of the Project Citizen model and to analyze its effectiveness in civic education within higher education settings. The research utilized a Research and Development (RD) approach, applying the ADDIE model which consists of five phases: Analysis, Design, Development, Implementation, and Evaluation. The development process involved one media expert, one subject matter expert, and 52 university students as participants. Validation from the media expert resulted in a score of 91%, indicating the media is very feasible. Similarly, the material expert gave a validation score of 94%, also categorized as very feasible. Student feedback, collected through questionnaires, yielded an effectiveness score of 83%, classifying the media as very effective. The findings demonstrate that the developed mobile-based Project Citizen learning media is both feasible and effective. It supports active civic engagement and structured learning, aligning well with the objectives of civic education in higher education institutions. The mobile-based Project Citizen media is a viable and effective tool for enhancing civic education. Its integration into the curriculum can facilitate meaningful student participation in democratic practices through project-based learning.